The power of leadership for learning: Developing niche-Malaysian teachers’ leadership competency model - Kho, Fanny Chee Yuet; Yusof, Hamidah; Syed Mohamad, Syed Ismail (2015)
Good teachers are learners and leaders, not only in their own classroom but in relation to their colleagues and their communities.Thus, the main purpose of this study was to develop an empirically substantiated Teachers’ Leadership Competency Model (TLCM) as well as to identify Teachers’ Leadership Competencies (TLC) that contribute to development of teacher leaders in Malaysian schools. The Structural Equation Modelling using AMOS Version 22 was applied to test the model. Exploratory Factor Analysis was utilized to identify the underpinning factors while Confirmatory Factor Analysis was exerted to examine the structural model. The findings indicate that teacher leaders’ roles positively and continuously influences teachers’ leadership competencies which will enhance teachers’ commitment to change their roles as classroom-based to school-based teacher leaders.This also implies that the teacher leaders’ role is a critical component in shifting the paradigm of teachers’ isolation to collaboration in Malaysian classrooms setting. The findings of TLCM will also benefit educational practitioners in designing Teacher Education Model for Malaysia.